Share market forecasting with LSTM neural network and sentimental trend prediction - Rony, Ismail Hossain; Anik, Ahsan Ahmed; Asif, Abdullah Al; Muhammad, Sayeed (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.